Analisis Etanol dalam Hair Tonic dan Hair Spray secara Kromatografi Gas - Endang Sri Rejeki (Jurnal Farmasi Indonesia, 2010)
Hair tonic and hair spray is a cosmetic for hair treatment. Hair tonic is a cosmetic treatment of the scalp and hair which is used after shampooing or when the scalp is clean. Hair spray is a cosmetic preparation used to strengthen temporary on hair that has been formed previously. The aim of the study was to determine the ethanol content in hair tonic and hair spray by gas chromatography. The quantitative analysis method used in this study was internal standard. The experiment began with looking for appropriate analysis. The chosen analysis condition was then used for quantitative analysis. The calibration curve equation was used to determine the ethanol content in hair tonic and hair spray samples. The results showed that the chosen analysis condition to determine the ethanol content in hair tonic and hair spray were: column temperature 50oC, injector temperature 70oC, detector temperature 100oC, and gas pressure 80 kPa. The ethanol content obtained in hair tonic sample was 15,2365% Â± 0,2475, while in hair spray sample was 17,2528% Â± 0,5765.